2017
DOI: 10.1021/acs.macromol.7b01867
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Study of Regio-Defects in the Copolymerization of Propylene Oxide/Carbonyl Sulfide Catalyzed by (Salen)CrX Complexes

Abstract: Small quantities of regio-defects in a regio-/stereoregular polymer weaken its tacticity and properties. This work clarified the origin of the regio-defect in the process of synthesizing poly­(monothiocarbonate) through the copolymerization of propylene oxide (PO) and carbonyl sulfide (COS) catalyzed by a (salen)­CrCl complex accompanied by bis­(triphenyl­phosphoranylidene)­ammonium chloride ([PPN]­Cl). Quantitative characterization results from the MALDI-TOF-MS and 1H (13C) NMR spectroscopy suggested that the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 43 publications
0
26
0
Order By: Relevance
“…13a, b ) revealed that the copolymer contained two secondary –OH end groups with minimal regio-defect (one dithiocarbonate unit) 40 . These results were indicative of inclusively regioselective attack of the sulfur anion to the CH 2 site of PO, and thus the sole production of the T–H diad via the organocatalysis 40 . In the presence of BnOH, only one distribution of α-OBn, ω-OH copolymer-terminated [BnO + (PO + COS) n + H + K + ] (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…13a, b ) revealed that the copolymer contained two secondary –OH end groups with minimal regio-defect (one dithiocarbonate unit) 40 . These results were indicative of inclusively regioselective attack of the sulfur anion to the CH 2 site of PO, and thus the sole production of the T–H diad via the organocatalysis 40 . In the presence of BnOH, only one distribution of α-OBn, ω-OH copolymer-terminated [BnO + (PO + COS) n + H + K + ] (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…6 ) could also initiate the copolymerization via the similar activation route of BnOH by TU/LB pair. Such H 2 O initiation led to the formation of the end –S(O=C)–OH group, which was thermodynamically unstable and thus converted to –SH group via decarboxylation process 6 , 40 . Since the end –SH group has the stronger acidity than –OH group, it was rapidly deprotonated, generating bifunctional initiator for further chain growth, a copolymer with two end secondary –OH groups and one dithiocarbonate unit ( f ) was produced, which was clearly revealed by Fig.…”
Section: Resultsmentioning
confidence: 99%
“…It was found that a chain transfer agent can cause a decrease in molecular weight while the conversion rate remains comparable. The origin of the regional defects of carbonyl sulfide/propylene oxide copolymerization catalyzed by the (Salen)CrCl/[PPN]Cl system was reported by Li et al . An asymmetric Cr(III) bis‐Schiff base complex was developed for the solventless ROCOP of CHO and maleic anhydride in the presence of co‐catalyst 4‐(dimethylamino)pyridine.…”
Section: Introductionmentioning
confidence: 99%
“…Since our first work on the alternating copolymerization of COS and propylene oxide (PO) [ 10 ], the conversion of COS to polymers has made significant advances [ 6 , 16 ]. However, reports on constructing block copolymers containing poly(monothiocarbonate) block are rare [ 20 , 23 ]. Ren and coworkers [ 20 ] reported the synthesis of a tri-block copolymer, poly(ethylene monothiocarbonate)- b -poly(propylene monothiocarbonate)- b -poly(ethylene monothiocarbonate) (PEMC- b -PPMC- b -PEMC), catalyzed by a highly active bifunctional (salen)Cr(III) complex with subsequent adding of monomers.…”
Section: Introductionmentioning
confidence: 99%
“…Ren and coworkers [ 20 ] reported the synthesis of a tri-block copolymer, poly(ethylene monothiocarbonate)- b -poly(propylene monothiocarbonate)- b -poly(ethylene monothiocarbonate) (PEMC- b -PPMC- b -PEMC), catalyzed by a highly active bifunctional (salen)Cr(III) complex with subsequent adding of monomers. Very recently, our group [ 23 ] reported a ABA block copolymer with precise structure, polystyrene- b -poly(propylene monothiocarbonate)- b -polystyrene (PS- b -PPTMC- b -PS) via atom transfer radical polymerization (ATRP) through several operation steps. Unfortunately, metal residues of the catalyst in these copolymers limited their potential applications [ 10 , 19 , 20 , 23 ].…”
Section: Introductionmentioning
confidence: 99%